2001
DOI: 10.1097/00005768-200109000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of training on NIRS muscle oxygen saturation during submaximal exercise

Abstract: The training-induced adaptation in blood lactate influences IR-SO(2) during mild- to hard-intensity exercise. Thus, NIRS could be used as a noninvasive monitoring of training-induced adaptations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
2
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 30 publications
6
52
2
9
Order By: Relevance
“…In their study, a short-term, highintensity cycling training program was administered for 3 weeks. Costes et al 18) also reported a lower decrease of StO 2 during mild to high intensity exercise. In their study, the untrained subjects trained 6 days a week for 4 weeks at 70-80% of the subject's maximal heart rate.…”
Section: Discussionmentioning
confidence: 88%
“…In their study, a short-term, highintensity cycling training program was administered for 3 weeks. Costes et al 18) also reported a lower decrease of StO 2 during mild to high intensity exercise. In their study, the untrained subjects trained 6 days a week for 4 weeks at 70-80% of the subject's maximal heart rate.…”
Section: Discussionmentioning
confidence: 88%
“…Limited studies have reported the effect of training on local muscle oxygenation measured by NIRS [17][18][19][20] . Furthermore, most of these studies used oxy-Hb/Mb to evaluate the local muscle oxygenation during exercise [17][18] or the recovery time after occlusion 19) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of these studies used oxy-Hb/Mb to evaluate the local muscle oxygenation during exercise [17][18] or the recovery time after occlusion 19) . In this study, we used deoxy-Hb/Mb to evaluate muscle deoxygenation level because this signal is regarded as being essentially insensitive to change in blood volume 15) .…”
Section: Discussionmentioning
confidence: 99%
“…44 It is also probable that a reduction of blood lactate accumulation Pelvic floor muscle training for women and the attenuation of muscle oxygen desaturation can be achieved when training regimens improve muscle oxidative metabolism. 45 In the context of new technology, dynamic magnetic resonance imaging of the pelvic floor can now provide novel information on the anatomy and structural integrity of the components of the pelvic floor. 46 Several investigators are using near infrared spectroscopy (NIRS) to monitor skeletal muscle function and the effects of exercise.…”
Section: Future Directionsmentioning
confidence: 99%